2020
DOI: 10.1039/d0ra02282a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and insight into the structure–activity relationships of 2-phenylbenzimidazoles as prospective anticancer agents

Abstract: Three series of 2-phenylbenzimidazoles obtained under simple and convenient pathways, were used to elucidate their SARs against three cancer cell lines: A549, MDA-MB-231 and PC3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Unfortunately, the reaction was unsuccessful in providing the expected product 7 and the imidazole 6 was obtained instead (Scheme 1). An earlier report 28 revealed that the use of meta-/para -substituted chalcones gives benzodiazepines rather than imidazoles. 29 Owing to the presence of the o -benzyl unit in chalcone 3m , steric hindrance may be the reason for the failure to obtain benzodiazepine 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the reaction was unsuccessful in providing the expected product 7 and the imidazole 6 was obtained instead (Scheme 1). An earlier report 28 revealed that the use of meta-/para -substituted chalcones gives benzodiazepines rather than imidazoles. 29 Owing to the presence of the o -benzyl unit in chalcone 3m , steric hindrance may be the reason for the failure to obtain benzodiazepine 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of ligands L 1 – L 5 was described in our previous reports [31,32], and for convenience of information searching, their identified characteristics are listed below.…”
Section: Methodsmentioning
confidence: 99%
“…The benzimidazole derivatives shown in scheme 1 were synthesized by a condensation reaction between o-phenylenediamine and benzaldehyde in the presence of Na 2 S 2 O 5 as an oxidation agent [31]. The yields obtained after purification ranged from 70% to 90%.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…10 Huynh and coworkers synthesized several new derivatives of 2-phenylbenzimidazole with a various range of substituents on the C-5, C-2, and C-6 positions of 2-phenylbenzimidazole with the condensation of o-phenylenediamines and different aldehydes and afterwards to illustrate their structure-activity relationship (SAR) upon three cancer cell lines:PC3, MDA-MB-231and A54. 11 On the other hand, quantitative structure-activity relationship studies have obtained a fundamental position within medicine chemistry. In QSAR analysis, one or more molecular descriptors are described to the molecular activity using statistical analysis.…”
Section: Introductionmentioning
confidence: 99%